Natural SARS-CoV-2 Infection Affects Neutralizing Activity in Saliva of Vaccinees - Garziano, Micaela; Utyro, Olga; Poliseno, Mariacristina; Santantonio, Teresa Antonia; Saulle, Irma; Strizzi, Sergio; Lo Caputo, Sergio; Clerici, Mario; Introini, Andrea; Biasin, Mara (Frontiers in immunology, 2022)
SARS-CoV-2 transmission mainly occurs through exposure of the upper airway mucosa to infected secretions such as saliva, which are excreted by an infected person. Thus, oral mucosal immunity plays a central role in the prevention of and early defense against SARS-CoV-2 infection. Although virus-specific antibody response has been extensively investigated in blood samples of SARS-CoV-2-infected patients and vaccinees, local humoral immunity in the oral cavity and its relationship to systemic antibody levels needs to be further addressed. We fine-tuned a virus neutralization assay (vNTA) to measure the neutralizing activity (NA) of plasma and saliva samples from 20 SARS-CoV-2-infected (SI), 40 SARS-CoV-2-vaccinated (SV), and 28 SARS-CoV-2-vaccinated subjects with a history of infection (SIV) using the "wild type" SARS-CoV-2 lineage B.1 (EU) and the Delta (B.1.617.2) strains. To validate the vNTA results, the presence of neutralizing antibodies (NAbs) to the spike receptor binding domain (RBD) was evaluated with an ELISA assay. NA to SARS-CoV-2 lineage B.1 (EU) was present in plasma samples from all the tested subjects, with higher titers in SIV compared to both SI and SV. Conversely, NA was detected in saliva samples from 10.3% SV, 45% SI, and 92.6% SIV, with significantly lower titers in SV compared to both SI and SIV. The detection of NAbs in saliva reflected its reduced NA in SV. The difference in NA of plasma vs. saliva was confirmed in a vNTA where the SARS-CoV-2 B.1 and Delta strains were tested head-to-head, which also revealed a reduced NA of both specimens compared to the B.1 variant. The administration of SARS-CoV-2 vaccines was associated with limited virus NA in the oral cavity, as measured in saliva and in comparison to plasma. This difference was more evident in vaccinees without a history of SARS-CoV-2 infection, possibly highlighting the importance of local exposure at the site of virus acquisition to effectively prevent the infection and block its spread. Nevertheless, the presence of immune escape mutations as possibly represented by the SARS-CoV-2 Delta variant negatively affects both local and systemic efficacy of NA associated with vaccination.